2016
DOI: 10.1007/s10265-016-0832-1
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellin stimulates regrowth after defoliation of sheepgrass (Leymus chinensis) by regulating expression of fructan-related genes

Abstract: Gibberellins (GAs) affect forage growth and development; however, it is largely unknown how GAs regulate the metabolism of fructan (an important polysaccharide reserve in many cereals) and the regrowth of forage plants after defoliation. To explore the mechanism of the responses of defoliated sheepgrass [Leymus chinensis (Trin.) Tzvel] to GA, we sprayed defoliated sheepgrass with GA3 and/or paclobutrazol (PAC; an inhibitor of GA biosynthesis) and analyzed the growth characteristics, carbohydrate contents, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…GA 3 treatment showed the highest promoting effect on seed germination and seedling growth in Capparis spinosa at 360.9 μM 7 , Trigonella foenum-graecum at 180.4 μM 11 , and 721.8–1443.5 μM for Parthenium argentatum Gray 39 . The yield attributes of Helianthus annuus L. 19 and Triticum aestivum L. 12 were also increased by seed treatment with 10–100 μM GA 3 for 8 h. In previous studies on L. chinensis , GA spraying at various growth stages remarkably promoted plant growth and grass production 40–42 . In this study, we showed that seed priming with GA 3 significantly promoted plant growth (Figs 2, 4) and enhanced grass production (Figs 3, 5) in L. chinensis , in both pot and field experiments.…”
Section: Discussionmentioning
confidence: 81%
“…GA 3 treatment showed the highest promoting effect on seed germination and seedling growth in Capparis spinosa at 360.9 μM 7 , Trigonella foenum-graecum at 180.4 μM 11 , and 721.8–1443.5 μM for Parthenium argentatum Gray 39 . The yield attributes of Helianthus annuus L. 19 and Triticum aestivum L. 12 were also increased by seed treatment with 10–100 μM GA 3 for 8 h. In previous studies on L. chinensis , GA spraying at various growth stages remarkably promoted plant growth and grass production 40–42 . In this study, we showed that seed priming with GA 3 significantly promoted plant growth (Figs 2, 4) and enhanced grass production (Figs 3, 5) in L. chinensis , in both pot and field experiments.…”
Section: Discussionmentioning
confidence: 81%
“…Sucrose content was measured by using the resorcinol method and estimated on the basis of the absorbance at a wavelength of 480 nm (Shi et al , 2016). Fructose content was quantified according to the method published elsewhere (Cai et al , 2016). Total soluble sugar analysis was performed by using the anthrone sulfuric acid method (Lei et al , 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Sucrose and nitrate, whose levels decreased and increased, respectively, following defoliation, might act in concert as signals to trigger protein and fructan degradation ( Marx et al , 1997 ; Müller et al , 2000 ; Morcuende et al , 2004 ; Lothier et al , 2010 ; Ould-Ahmed et al , 2014 ). Other factors are involved in the control of protein and fructan metabolisms in relation to regrowth after defoliation, such as gibberellins ( Morvan et al , 1997 ; Cai et al , 2016 ), abscisic acid ( Yang et al , 2004 ), and/or cytokinin ( Wang et al , 2013 ), which do not act as independent factors but are components of multiple signalling pathways.…”
Section: Discussionmentioning
confidence: 99%